Formulating A Legal Model for Governing Soil Fitness in Housing Development Projects (S/O 14175) - Md Dahlan, Nuarrual Hilal; Mohd Md Isa @ Yusuff, Yusramizza; Mohd Khalid, Al-Hanisham (UUM, 2023)
Landslides in housing development projects have caused property damage and loss of life. It is a trite fact that, in Malaysia, soil problems have negatively impacted the residents' lives and property. The main objective of this research is to analyse the legal provisions in housing development laws that have a bearing on soil problems in housing development projects. This research proposes a legal model for governing soil fitness in housing development areas. Qualitative social research and legal research methodologies were used in this research. The research suggests certain legal reforms relating to housing development law, viz land, planning, building, and housing development laws, to face soil problems and protect the rights of house residents.